Research in Education: tensions, dilemmas and overcoming dynamics - Cachapuz, António (Revista Hipótese, 2016)
Essentially, the problems of Research in Education can be categorized into three types: relevance, quality and organization. No record here the issues of funding, not to consider them irrelevant but for not having sufficient information to allow me a minimally objective approach. On the subject I will simply refer to what my reflection on the experience advises me, namely: best research budgets do not necessarily lead to better results.